2014
DOI: 10.1080/07474946.2014.856635
|View full text |Cite
|
Sign up to set email alerts
|

Flexibly Monitoring Group Sequential Survival Trials When Testing is Based Upon a Weighted Log-Rank Statistic

Abstract: We consider the repeated group sequential testing of a survival endpoint with a time-varying treatment effect using a weighted logrank statistic. The emphasis of this paper is on the monitoring of this statistic where information growth is non-linear. We propose using a constrained boundaries approach to maintain the planned operating characteristics of a group sequential design. A simulation study is presented to demonstrate the operating characteristics of the method together with a case study to illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In this case, the surrogate information fraction based on the number of events provides a conservative procedure, because the PPPW statistic emphasizes the early events. More generally, Brummel and Gillen proposed a prediction algorithm of information fraction in the G ρ , γ family. Although Tsiatis showed that the G ρ , γ statistic has an independent increments structure, the information fraction depends not only on the number of events but also on the event timing and size of the risk set at the event times .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the surrogate information fraction based on the number of events provides a conservative procedure, because the PPPW statistic emphasizes the early events. More generally, Brummel and Gillen proposed a prediction algorithm of information fraction in the G ρ , γ family. Although Tsiatis showed that the G ρ , γ statistic has an independent increments structure, the information fraction depends not only on the number of events but also on the event timing and size of the risk set at the event times .…”
Section: Introductionmentioning
confidence: 99%
“…More generally, Brummel and Gillen proposed a prediction algorithm of information fraction in the G ρ , γ family. Although Tsiatis showed that the G ρ , γ statistic has an independent increments structure, the information fraction depends not only on the number of events but also on the event timing and size of the risk set at the event times . Therefore, Brummel and Gillen's algorithm requires parametric assumptions regarding the entry, survival, and censoring distributions.…”
Section: Introductionmentioning
confidence: 99%
“…The realization of a censoring pattern in a study is a convolution of three distinct distributions—enrollment, LTFU, and TTE distributions. Since censoring affects IF, a precise knowledge of these three distributions is necessary to calculate IF 18‐21 . However, since these distributions cannot be predicted precisely at the design stage, an obvious strategy would be to evaluate all possible censoring scenarios and then to choose the minimum IF to preserve the overall size.…”
Section: Information Fraction For a Fleming‐harrington Testmentioning
confidence: 99%
“…However, estimation of IF, which determines the rejection boundaries for testing at the interim analysis, remains a challenging problem: For the SLR test, the IF is proportional to the number of interim events; but in general, this relationship is not guaranteed to hold for the WLR test 18 . As Brummel and Gillen 19 pointed out, if IFs accrued at the interim analyses are not correctly estimated at the design stage, then power and type I error will differ from the originally targeted value: If IF is underestimated, then the overall size of the test may be inflated; on the contrary, if IF is overestimated, then the overall power of the test may be compromised. The focus of this article is to correctly estimate IF for FH(ρ,γ) test in a group‐sequential trial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation